Novel Thiosemicarbazone Derivatives: In Vitro and In Silico Evaluation as Potential MAO-B Inhibitors - Derya Osmaniye (MDPI AG, 2021)
MAO-B inhibitors are frequently used in the treatment of neurodegenerative diseases such as Parkinson’s and Alzheimer’s. Due to the limited number of compounds available in this field, there is a need to develop new compounds. In the recent works, it was shown that various thiosemicarbazone derivatives show hMAO inhibitory activity in the range of micromolar concentration. It is thought that benzofuran and benzothiophene structures may mimic structures such as indane and indanone, which are frequently found in the structures of such inhibitors. Based on this view, new benzofuran/benzothiophene and thiosemicarbazone hybrid compounds were synthesized, characterized and screened for their hMAO-A and hMAO-B inhibitory activity by an in vitro fluorometric method. The compounds including methoxyethyl substituent (2b and 2h) were found to be the most effective agents in the series against MAO-B enzyme with the IC50 value of 0.042 ± 0.002 µM and 0.056 ± 0.002 µM, respectively. The mechanism of hMAO-B inhibition of compounds 2b and 2h was investigated by Lineweaver–Burk graphics. Compounds 2b and 2h were reversible and non-competitive inhibitors with similar inhibition features as the substrates. The Ki values of compounds 2b and 2h were calculated as 0.035 µM and 0.046 µM, respectively, with the help of secondary plots. The docking study of compound 2b and 2h revealed that there is a strong interaction between the active sites of hMAO-B and analyzed compound.